(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
Eosclerocalyptus tapinocephalus (Cabrera) from the Huayquerian (Late Miocene) of the Pampean region, was known previously only from the type material. The recent finding of a well preserved specimen, mainly the caudal tube and limb bones, allows improved knowledge of its morphology and comparison with related forms, particularly Eosclerocalyptus proximus (Moreno and Mercerat) of the "Araucanian" (Late Miocene-Early Pliocene) from the northwest of Argentina, and Neosclerocalyptus Paula Couto (Pleistocene of Argentina, Paraguay and Uruguay). Our observations support the recent proposal of Perea to include Hoplophractus Cabrera within Eosclerocalyptus C. Ameghino. Morphologically, E. tapinocephalus is characterized by: a) the parieto-occipital region of the skull tilting posteriorly; b) the low zygomatic arch descending towards the orbital notch; c) the lateral osteoderms of the dorsal carapace, with anterior peripheral figures of greater development than the posterior ones; d) dorsal carapace of dorsal contour similar to the that of E. proximus; e) caudal tube similar to that of E. proximus but with less development of the small peripheral figures; f) femoral morphology intermediate between Propalaehoplophorus and Neosclerocalyptus. Finally, and from a palaeozoogeographic and stratigraphic point of view, Eosclerocalyptus tapinocephalus represents (together with E. proximus) the first certain species of the tribe Hoplophorini, limited to the Huayquerian Stage (Late Miocene; ca. 8.7-6.8 Ma) of the central area of the Buenos Aires province, characterized by the presence of open environments (savannas, grasslands and herbaceous steppes).